Urban management in a European context - Irena Bačlija (Urbani Izziv, 2011)
Since the works of John Rex (1968), Ray Pahl (1970, 1975, 1979) and Peter Williams (1976, 1978), the concept of urban management and its (re)conceptualisation has reached beyond one discipline and beyond its normative definition. Many authors have attempted to offer an adequate definition; however, convergence on this topic has never occurred. As Richard Stren (1993) notes, the vagueness of the concept exists despite analytical and comparative work on this subdiscipline. To date, Williams’ (1978) question of whether urban management is a framework for study, a process or a structure remains unanswered. This paper explains the (re)conceptualisation of urban management as a reform of city administration and claims that its primary task is to bring about a much needed balance between the social and economic development of the city. In addition, the empirical study “Urban management in EU cities” presented in this paper offers several conclusions. The most relevant conclusion is that EU cities already commonly employ this concept of urban management. Other conclusions are that, if a city is large, there is a greater possibility that the city administration will adopt urban management; that, if the city is more successful economically (Lisbon benchmark), there is a greater possibility that the city administration will adopt urban management; and that the city’s power (Index of City Power) and urban management (Urban Management Index) are not correlated. This final conclusion could imply that the autonomy of city government is irrelevant for successfully implementing urban management. Based on the survey conducted, it can be concluded that implementing an urban management concept, when that concept is defined as proposed in this paper, has a positive effect on some aspects of a city’s performance.